At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine which hyperbola has its foci farthest from its center, we need to find the distance [tex]\(c\)[/tex] from the center to each focus for each given hyperbola equation. The general form of a hyperbola is:
[tex]\[ \frac{(x-h)^2}{a^2} - \frac{(y-k)^2}{b^2} = 1 \quad \text{or} \quad \frac{(y-k)^2}{a^2} - \frac{(x-h)^2}{b^2} = 1 \][/tex]
For a hyperbola, [tex]\(c\)[/tex] is given by:
[tex]\[ c = \sqrt{a^2 + b^2} \][/tex]
Let's calculate [tex]\(c\)[/tex] for each hyperbola equation provided.
Equation A:
[tex]\[ \frac{(z-2)^2}{8^2}-\frac{(y-1)^2}{7^2}=1 \][/tex]
Here, [tex]\(a = 8\)[/tex] and [tex]\(b = 7\)[/tex].
[tex]\[ c = \sqrt{8^2 + 7^2} = \sqrt{64 + 49} = \sqrt{113} \approx 10.63 \][/tex]
Equation B:
[tex]\[ \frac{(2 y+4)^2}{19^2}-\frac{(2 x-6)^2}{11^2}=1 \][/tex]
Here, [tex]\(a = 19\)[/tex] and [tex]\(b = 11\)[/tex].
[tex]\[ c = \sqrt{19^2 + 11^2} = \sqrt{361 + 121} = \sqrt{482} \approx 21.95 \][/tex]
Equation C:
[tex]\[ \frac{(y-1)^2}{6^2}-\frac{(x-2)^2}{9^2}=1 \][/tex]
Here, [tex]\(a = 6\)[/tex] and [tex]\(b = 9\)[/tex].
[tex]\[ c = \sqrt{6^2 + 9^2} = \sqrt{36 + 81} = \sqrt{117} \approx 10.82 \][/tex]
Equation D:
[tex]\[ \frac{(y-5)^2}{5^2}-\frac{(2 x+6)^2}{10^2}=1 \][/tex]
Here, [tex]\(a = 5\)[/tex] and [tex]\(b = 10\)[/tex].
[tex]\[ c = \sqrt{5^2 + 10^2} = \sqrt{25 + 100} = \sqrt{125} \approx 11.18 \][/tex]
Comparing the values of [tex]\(c\)[/tex]:
[tex]\[ c_A \approx 10.63, \quad c_B \approx 21.95, \quad c_C \approx 10.82, \quad c_D \approx 11.18 \][/tex]
The hyperbola with the largest [tex]\(c\)[/tex] value is Equation B, as:
[tex]\[ c_B \approx 21.95 \][/tex]
Therefore, the correct answer is:
B. [tex]\(\frac{(2 y+4)^2}{19^2}-\frac{(2 x-6)^2}{11^2}=1\)[/tex]
[tex]\[ \frac{(x-h)^2}{a^2} - \frac{(y-k)^2}{b^2} = 1 \quad \text{or} \quad \frac{(y-k)^2}{a^2} - \frac{(x-h)^2}{b^2} = 1 \][/tex]
For a hyperbola, [tex]\(c\)[/tex] is given by:
[tex]\[ c = \sqrt{a^2 + b^2} \][/tex]
Let's calculate [tex]\(c\)[/tex] for each hyperbola equation provided.
Equation A:
[tex]\[ \frac{(z-2)^2}{8^2}-\frac{(y-1)^2}{7^2}=1 \][/tex]
Here, [tex]\(a = 8\)[/tex] and [tex]\(b = 7\)[/tex].
[tex]\[ c = \sqrt{8^2 + 7^2} = \sqrt{64 + 49} = \sqrt{113} \approx 10.63 \][/tex]
Equation B:
[tex]\[ \frac{(2 y+4)^2}{19^2}-\frac{(2 x-6)^2}{11^2}=1 \][/tex]
Here, [tex]\(a = 19\)[/tex] and [tex]\(b = 11\)[/tex].
[tex]\[ c = \sqrt{19^2 + 11^2} = \sqrt{361 + 121} = \sqrt{482} \approx 21.95 \][/tex]
Equation C:
[tex]\[ \frac{(y-1)^2}{6^2}-\frac{(x-2)^2}{9^2}=1 \][/tex]
Here, [tex]\(a = 6\)[/tex] and [tex]\(b = 9\)[/tex].
[tex]\[ c = \sqrt{6^2 + 9^2} = \sqrt{36 + 81} = \sqrt{117} \approx 10.82 \][/tex]
Equation D:
[tex]\[ \frac{(y-5)^2}{5^2}-\frac{(2 x+6)^2}{10^2}=1 \][/tex]
Here, [tex]\(a = 5\)[/tex] and [tex]\(b = 10\)[/tex].
[tex]\[ c = \sqrt{5^2 + 10^2} = \sqrt{25 + 100} = \sqrt{125} \approx 11.18 \][/tex]
Comparing the values of [tex]\(c\)[/tex]:
[tex]\[ c_A \approx 10.63, \quad c_B \approx 21.95, \quad c_C \approx 10.82, \quad c_D \approx 11.18 \][/tex]
The hyperbola with the largest [tex]\(c\)[/tex] value is Equation B, as:
[tex]\[ c_B \approx 21.95 \][/tex]
Therefore, the correct answer is:
B. [tex]\(\frac{(2 y+4)^2}{19^2}-\frac{(2 x-6)^2}{11^2}=1\)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.